An IoT-based remote monitoring system for electrical power consumption via web-application - Alulema, Darwin (2018)
Electricity is a fundamental need of the human being that is commonly used for domestic, industrial and agricultural purposes. In this sense, the waste of energy generates millionaire losses for the countries. Technological solutions such as the Internet of Things (IoT) allows connecting the physical with the digital world in order to optimize resources and in this particular case, manage and/or monitor the energy consumption. In addition, the advance of micro and nanoelectronics has allowed the development of communication modules such as the XBee that allows the implementation of a wireless sensor network quickly and efficiently with minimal energy consumption being widely used for monitoring and control tasks. The presented prototype takes advantage of the previously mentioned advantages by developing a hardware and software solution. It allows remote monitoring of electricity consumption in a home through a scalable and modular platform using XBee technology and a customized protocol for data communication between the four modules that make up the system. Results are presented that demonstrate the accuracy of the prototype compared to the readings obtained with a conventional electricity meter. © 2018 IEEE.